A Vessel for Change: Endothelial Dysfunction in Cerebral Small Vessel Disease. Issue 4 (April 2021) - Quick, Sophie; Moss, Jonathan; Rajani, Rikesh M.; Williams, Anna
Abstract : The blood vessels of the brain are lined with endothelial cells and it has been long known that these help to regulate blood flow to the brain. However, there is increasing evidence that these cells also interact with the surrounding brain tissue. These interactions change when the endothelial cells become dysfunctional and have an impact in diseases such as cerebral small vessel disease, the leading cause of vascular dementia. In this review, we focus on what endothelial dysfunction is, what causes it, how it leads to surrounding brain pathology, how researchers can investigate it with current models, and where this might lead in the future for dementia therapies. Highlights: Endothelial cells lining the brain's blood vessels have been under-appreciated as players in brain diseases: they not only control blood flow and blood–brain barrier function, but also, their cellular interactions influence surrounding brain tissue. Cerebral small vessel disease (SVD) is a common form of vascular dementia, where dysfunctional endothelial cells lead to surrounding white matter changes, an early feature of the disease, which associates with clinical severity. We describe preclinical models reflecting genetic and/or environmental influences of SVD and summarise the links found between endothelial dysfunction and white matter changes, with suggestions to improve choice and use of these models.